IN SEARCH OF CASH‐FLOW PRICING. (14th December 2015) - Fabozzi, Frank J.; Chen, K. C.; Ma, K. C.; West, Jessica
Abstract: There are varying views on the relative importance of cash flow versus earnings in the pricing of stocks. In this article, we identify which financial metric—cash flow or earnings—is more often used by investors in equity valuation and then investigate why investors focus on one more than the other. Our prior is that the practice of deviating from cash‐flow pricing, if it exists, can be explained by either rational herding or information cascades. We find that although stock prices are, on average, affected by short‐term earnings, cash‐flow pricing is used primarily to price what we classify as "negative" stocks—stocks that are generally characterized as illiquid, mispriced, or having a shorter trading history, negative earnings, or negative market performance. We find evidence consistent with the rational argument of information cascades. For stocks under close public scrutiny, investors tend to follow the decisions of others and feel compelled to conform to the majority even though their private information suggests otherwise. In the end, the choice to value stocks with either earnings or cash flow is still a rational one.